Validity of Al-Qur'an-Based Integrated Inquiry-Based Electrolyte and Nonelectrolyte Solution Module for Class X Madrasah Aliyah (MA) - Rosa Karlina; Iryani Iryani (Journal of Educational Sciences, 2022)
This study aims to develop and determine the validity of the Al-Qur'an integrated guided inquiry-based electrolyte and nonelectrolyte solution module for class X Madrasah Aliyah (MA). This research uses the Plomp development model, which consists of three stages: preliminary research, prototyping stage, and assessment phase. Research instrument validity test in the form of a questionnaire given to lecturers and teachers. The validity value is calculated using the Aiken formula, and the study results get a product validity value of 0.87, which can be categorized as valid. Based on the analysis of the validity data, it can be concluded that the electrolyte and nonelectrolyte solution module based on the integrated guided inquiry of the Qur'an for class X Madrasah Aliyah (MA) is valid and can be tested further, namely, the practicality and effectiveness of the module.